2018
DOI: 10.1002/cpdd.584
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, Pharmacodynamics, and Safety of Subcutaneous Bapineuzumab: A Single‐Ascending‐Dose Study in Patients With Mild to Moderate Alzheimer Disease

Abstract: This study was designed to evaluate the safety, tolerability, pharmacokinetics, and pharmacodynamics of single ascending subcutaneous doses of bapineuzumab in patients with mild to moderate Alzheimer disease. Forty patients were randomized across 5 cohorts (5 mg, 10 mg, 20 mg, 40 mg, 80 mg; 8 patients each [bapineuzumab 6; placebo 2]). The incidence of treatment-emergent adverse events (TEAEs) was higher in pooled bapineuzumab cohorts (83%) than in the pooled placebo group (27.7%). Most common TEAEs in the bap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Based on these observations, bapineuzumab successfully reached phase III clinical trial . However, all bapineuzumab studies after concluding the results were terminated in August 2012, due to the evidence of low efficacy and increased the occurrence of magnetic resonance imaging (MRI) abnormalities, known as amyloid‐related imaging abnormalities attributed to edema or effusion (ARIA‐E) with high doses of bapineuzumab and APOE‐ε4 gene carriers …”
Section: Alternative Interventions To Prevent Aβ Accumulation By Immumentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these observations, bapineuzumab successfully reached phase III clinical trial . However, all bapineuzumab studies after concluding the results were terminated in August 2012, due to the evidence of low efficacy and increased the occurrence of magnetic resonance imaging (MRI) abnormalities, known as amyloid‐related imaging abnormalities attributed to edema or effusion (ARIA‐E) with high doses of bapineuzumab and APOE‐ε4 gene carriers …”
Section: Alternative Interventions To Prevent Aβ Accumulation By Immumentioning
confidence: 99%
“…119 However, all bapineuzumab studies after concluding the results were terminated in August 2012, 112 due to the evidence of low efficacy and increased the occurrence of magnetic resonance imaging (MRI) abnormalities, known as amyloid-related imaging abnormalities attributed to edema or effusion (ARIA-E) with high doses of bapineuzumab and APOE-ε4 gene carriers. 120,121 Another first-generation Aβ passive immunotherapy is solanezumab (LY2062430, Eli Lilly), an IgG1 mAb that is humanized from the parent murine antibody m266. Solanezumab targets the residues 16 to 26 at the middle region of Aβ peptide and has the ability to recognize the soluble monomers but not the fibrillary Aβ species.…”
mentioning
confidence: 99%
“…The first studied candidate monoclonal antibody was bapineuzumab, which targets the Aβ N-terminus and possesses a higher affinity for deposited amyloid plaques than soluble Aβ monomers (116,117). However, multiple studies and a meta-analysis conducted by Abushouk et al assessing the potential use of bapineuzumab in the treatment of AD, reported significant association with severe adverse events and no enhancement of cognitive decline, and therefore concluded that bapineuzumab is not recommended for use in the treatment of AD and clinical trials have since then been discontinued (117)(118)(119)(120)(121)(122)(123).…”
Section: Clinical Trialsmentioning
confidence: 99%
“…For example, in the case of immunotherapy, target activation could be demonstrated by the formation of antibody titers in plasma [156], and in the case of an antisense oligonucleotide, target activation may be demonstrated by a reduction in target protein levels [33,167]. For other types of drugs such as monoclonal antibodies against amyloid β [53][54][55][56][57][58][59][60][61][62][63], it may not be possible to demonstrate target activation, as the goal of these treatments is to clear the molecular target either by macrophage phagocytosis and complement activation or by altering the equilibrium of amyloid across the blood-brain barrier in favor of efflux from the brain to the blood [185].…”
Section: Target Activationmentioning
confidence: 99%
“…It appears that clinical outcomes are most frequently included (74%) as exploratory endpoints in early phase trials with NDD patients (Figure 1). These clinical outcome measures included disease rating scales (e.g., Alzheimer's Disease Assessment Scale-Cognitive Subscale (ADAS-Cog) [53,70,73,78], Mini-Mental State Examination (MMSE) [58,61], Revised Amyotrophic Lateral Sclerosis Functional Rating Scale (ALSFRS-R) [33,106,119], Neuronal Ceroid Lipofuscinosis Type 2 (CLN2) Clinical Rating Scale [143], Unified Huntington's Disease Rating Scale (UHDRS) [132], Hammersmith Functional Motor Scale Expanded (HFMSE) [167], and Movement Disorders Society Unified Parkinson Disease Rating Scale (MDS-UPDRS) [153,154,161]), pulmonary functioning evaluation [100,128] muscle power assessments [99,103,113], and quality of life questionnaires [68,120,152]. We would argue, however, that due to small samples sizes in early phase trials, potentially significant placebo effects or sometimes lack of a placebo control, and the relatively low sensitivity of these disease rating scales such instruments may at best be useful as safety biomarkers but not as outcome markers at this stage of clinical development.…”
Section: Clinical Responsementioning
confidence: 99%